Species-Specific Detection and Quantification of Erwinia pyrifoliae in Plants by a Direct SYBR Green Quantitative Real-Time PCR Assay - Yong Ju Jin; Hyun Gi Kong; Su In Yang; Hyeonheui Ham; Mi-Hyun Lee; Dong Suk Park (PhytoFrontiers, 2022)
The present study describes a SYBR Green real-time quantitative (q) PCR assay to detect Erwinia pyrifoliae in plants. E. pyrifoliae, first described in South Korea, is a phytopathogenic bacterial species in the genus Erwinia. In particular, specific detection, quantitation, and identification of E. pyrifoliae is still challenging, as symptoms resulting from its colonization of Asian pear blossoms are very similar to those caused by E. amylovora. E. pyrifoliae has biochemical, phenotypic, and genetic properties similar to those of E. amylovora. Moreover, other Erwinia species, including E. tasmaniensis and E. billingiae, are also detected by currently available molecular methods and with traditional methods as well. Therefore, in this study, previously published genome sequences of the genera Erwinia and Pantoea were compared to exploit species-specific genes for use as improved qPCR targets to detect E. pyrifoliae. In silico analyses of the selected gene and designed primer sequences, in conjunction with bio-SYBR Green real-time qPCR, confirmed the robustness of this newly developed assay. Consequently, the bio-SYBR Green real-time qPCR-based protocols developed here can be used for rapid and specific detection of E. pyrifoliae. They will potentially simplify and facilitate diagnosis and monitoring of this pathogen and guide plant disease management. [Figure: see text] Copyright © 2022 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.